Driven to Distraction: Extraneous Events and Underreaction to Earnings News - HIRSHLEIFER, DAVID; LIM, SONYA SEONGYEON; TEOH, SIEW HONG (Journal of Finance, 2009)
ABSTRACT Recent studies propose that limited investor attention causes market underreactions. This paper directly tests this explanation by measuring the information load faced by investors. The investor distraction hypothesis holds that extraneous news inhibits market reactions to relevant news. We find that the immediate price and volume reaction to a firm's earnings surprise is much weaker, and post‐announcement drift much stronger, when a greater number of same‐day earnings announcements are made by other firms. We evaluate the economic importance of distraction effects through a trading strategy, which yields substantial alphas. Industry‐unrelated news and large earnings surprises have a stronger distracting effect.